Numerical Study of Nanosecond Pulsed Plasma Actuator in Laminar Flat Plate Boundary Layer (Communications in Computational Physics, 2020)
Nanosecond (ns) pulsed dielectric barrier discharge (DBD) actuator in alaminar flat plate boundary layer is investigated numerically in an attempt to gainsome new insights into the understanding of ns DBD actuation mechanism. Specialemphasis is put on the examination, separation and comparison of behaviors of dischargeinduced micro shock wave and residual heat as well as on the investigationof response of external flow to the two effects. The shock wave is found to introducehighly transient, localized perturbation to the flow and be able to significantly alterthe flow pattern shortly after its initiation. The main flow tends to quickly recoverto close to its undisturbed state due to the transient nature of perturbation. However,with the shock decay and final disappearance, another perturbation source in thevicinity of discharge region, which contains contribution from both residual heat andshock, becomes increasingly pronounced and eventually develops into a perturbationwave train in the boundary layer. The perturbation is relatively weak and may not bea Tollmien-Schlichting (TS) wave and not trigger the laminar-turbulent transition ofboundary layer. Instead, it is more likely to manipulate the flow stability to achievethe strong control authority of this kind of actuation in the case of flow separation control.In addition, a parametric study over the different electrical and hydrodynamicparameters is also conducted.